Meta Analisis terhadap Tantangan dan Peluang dalam Implementasi Model Problem Based Learning pada Pelajaran IPS di Sekolah Dasar - Nadia Adillah Harpizon; Aramudin Aramudin; Rian Vebrianto; M. Fikri Hamdani; Khairul Saleh (Departement of Mathematics Education, 2024)
The purpose of this research is to quantify the impact of the problem-based learning (PBL) paradigm on primary school pupils' achievement in social subjects. With a focus on primary school pupils, this research intends to reevaluate the efficacy of the Problem Based Learning Learning paradigm in enhancing mathematical understanding. This study employed a meta-analysis via qualitative descriptive analysis approach, which entails examining or assessing published publications based on research findings. This meta-analysis found that, with a range of 0.03% to 0.71%, the Problem-Based Learning Learning model significantly improves students' learning outcomes in elementary school. When looking at the effect size in terms of education in the elementary school jejang category, the results of the meta-analysis indicate that there are learning outcomes of the social sciences (IPS) that are significantly impacted by the problem-based learning model. The average effect size is 1.302231. Accordingly, the result is Assuming that IPS makes good use of the Problem-Based Learning methodology to boost primary school pupils' performance in social studies,.